Effectiveness of using Listening Media Software (LMS) in teaching listening in EFL in Indonesia / Pegiawan Basopi ... [et al.] - Basopi, Pegiawan; Abdul Aziz, Roslina; -, Akmal (Universiti Teknologi MARA, Kedah, 2021)
The study seeks (1) to examine the effectiveness of using Listening Media Software (LMS) in improving different listening skills tested in the National Examination Listening Test (NELT) among third-grade students from a private senior high school in Indonesia and (2) to determine the effectiveness of LMS in improving the students’ overall listening comprehension. The study adopted a quasi-experimental design, involving 64 third-grade students of Madrasah Aliyah Muhammadiyah Al-Furqon Tasikmalaya, Indonesia, who were divided equally into a control group and an experimental group. Data were collected by means of a pre-test and a post-test. The results of the analysis indicate that the experimental group performed significantly better than the control group in different sections of the National Examination Listening Test (NELT). Paired sample t-test of the means of the pre-test and post-test scores of the experimental group, obtained a p value of α=0.000, thus, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. The study concludes that the use of LMS was effective in improving students’ overall listening comprehension of the third-grade students involved in this study.